Mechanical evaluation of a novel angle‐stable interlocking nail in a gap fracture model. Issue 8 (8th June 2022) - Deprey, Julie; Blondel, Margaux; Saban, Charles; Massenzio, Michel; Gauthier, Olivier; Moissonnier, Pierre; Viguier, Eric; Cachon, Thibaut
Abstract: Objective: To describe the mechanical characteristics of a novel angle‐stable interlocking nail (NAS‐ILN) and compare them to those of a locking compression plate (LCP) by using a gap‐fracture model. Study design: Experimental study. Sample population: Synthetic bone models. Methods: Synthetic bone models simulating a 50 mm diaphyseal comminuted canine tibial fracture were treated with either a novel angle‐stable interlocking nail (NAS‐ILN) or a locking compression plate (LCP). Maximal axial deformation and load to failure in compression and 4‐point bending, as well as maximal angular deformation, slack, and torque to failure in torsion, were statistically compared ( P < .05). Results: In compression, the maximal axial deformation was lower for NAS‐ILN (0.11 mm ± 0.03) than for LCP (1.10 mm ± 0.22) ( P < .0001). The ultimate load to failure was higher for NAS‐ILN (803.58 N ± 29.52) than for LCP (328.40 N ± 11.01) ( P < .0001). In torsion, the maximal angular deformation did not differ between NAS‐ILN (22.79° ± 1.48) and LCP (24.36° ± 1.45) ( P = .09). The ultimate torque to failure was higher for NAS‐ILN (22.45 Nm ± 0.24) than for LCP (19.10 Nm ± 1.36) ( P = .001). No slack was observed with NAS‐ILN. In 4‐point bending, the maximal axial deformation was lower for NAS‐ILN (3.19 mm ± 0.49) than for LCP (4.17 mm ± 0.34) ( P = .003). The ultimate bending moment was higher for NAS‐ILN (25.73 Nm, IQR [23.54‐26.86] Nm) than for LCP (16.29 Nm, IQR [15.66‐16.47] Nm) ( P = .002). Conclusion: The NAS‐ILN showed greater stiffness in compression and 4‐point bending, and a greater resistance to failure in compression, torsion, and 4‐point bending, than LCP. Clinical impact: Based on these results, NAS‐ILNs could be considered as alternative implants for the stabilization of comminuted fractures.